HARNESSING ENTREPRENEURIAL BRICOLAGE FOR MSME’S SUCCESS: INNOVATION AND ADAPTATION AT TANJUNG PENYU BEACH - Kustiningsih, Nanik; Nam, Le Hoai; Asy’ari, Vaizal (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2025)
This study explores the role of bricolage as a strategic mechanism in the entrepreneurial success of MSMEs at Tanjung Penyu Beach, Malang, which has transformed from an agricultural area into a tourist destination. This research addresses a gap in the literature, which has paid limited attention to the application of bricolage in the context of land-use changes and MSMEs adaptation in the tourism sector of developing countries. Most previous studies have focused on bricolage in the context of technological innovation or large-scale businesses, while its role in supporting MSMEs adaptation in resource-constrained regions remains underexplored. Using a qualitative approach through in-depth interviews, this research identifies how MSMEs in the region creatively utilize local resources following the conversion of agricultural land into a tourism site, providing opportunities for farmers to adapt to environmental changes. This research introduces new insights into how bricolage can be used as a flexible adaptation strategy to address changes in the business environment in developing coastal areas. The findings indicate that bricolage techniques enhance product innovation, leverage social networks, and create new value for MSMEs. However, a major challenge is the promotional strategy, which remains limited to local media, hindering the potential to attract more visitors. The study aims to provide new perspectives on how bricolage techniques can help MSMEs overcome resource constraints, innovate, and capitalize on opportunities in a dynamic context. This study offers insights into how bricolage can help overcome resource constraints and adapt to market changes, highlighting the need for more effective digital promotion strategies to enhance the appeal of Tanjung Penyu Beach as a tourist destination and maximize the success of MSMEs in the area.